Quality in Transition: the MBKM’s Effects on Teacher Education and Other Education-Related Programs - Faridah; Sriwidayani Syam; Irmawati (PT. Global Research Collaboration, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) policy was introduced to promote cross-disciplinary learning and enhance student competencies through experiential activities. While progressive in intent, its effect on educational quality, particularly in teacher education and related programs, remains contested. This qualitative case study critically examines the implementation of MBKM in teacher education, educational technology, non-formal education, and educational administration programs. Data were collected from the program head through in-depth interviews and analysis of relevant documents. The findings reveal that while MBKM provides expanded opportunities for student learning and skill development, its implementation often leads to fragmented learning experiences, misalignment between field activities and program learning outcomes, and challenges in maintaining core professional competencies. In teacher education, concerns center on the diminished coherence between theoretical foundations and practical placements, as well as the risk of weakening core teacher competencies resulting from insufficient integration of curricula and mentoring. Study programs often have limited involvement in MBKM management, resulting in inconsistent credit recognition and misalignment with intended learning outcomes. The results call for greater involvement of study programs in the design, supervision, and assessment of MBKM activities to ensure alignment with core competencies and preserve the integrity of professional preparation.